Quality by design-based development and validation of a stability-indicating RP-HPLC method for quantitative estimation of enzalutamide in eutectic mixtures - Wannur, Vishal Irappa; Patil, Archana S.; Sawadi, Bhavana; Koli, Rahul; Shaligram, Parth Shailendra; shet, Nagabhushan; Gonnade, Rajesh G. (SSC Plus, 2025)
Metastatic castration-resistant prostate cancer presents a significant clinical challenge, with Enzalutamide—an androgen receptor inhibitor—serving as a standard therapeutic agent. Despite its efficacy, poor aqueous solubility (Biopharmaceutics classification system Class II) limits its bioavailability, necessitating advanced formulation strategies. This study reports a robust and validated Reverse Phase High Performance Liquid Chromatography (RP-HPLC) method for quantifying enzalutamide in bulk and eutectic formulations. A Quality by Design framework employing a Box–Behnken design was used to optimize chromatographic parameters: 60% acetonitrile, 1 mL/min flow rate, 30°C column temperature, and 234 nm detection wavelength. The method exhibited strong linearity (2–12 µg/mL, r2 = 0.9985) with a limit of detection and limit of quantification of 0.464 and 1.40 µg/mL, respectively. Validation per International Council for Harmonisation Q2 (R1/R2) confirmed accuracy, precision, robustness, and system suitability. Forced degradation studies verified its stability-indicating capability. Eutectic mixtures with succinic acid, caffeine, and ferulic acid were prepared via liquid-assisted grinding and characterized using powder x-ray diffraction, confirming crystalline eutectic formation. Recovery ranged from 96.7% to 99.8%, supporting the method's applicability in routine analysis and formulation development. Greenness evaluation using various tools confirmed the method's low environmental impact and high operational feasibility. This validated RP-HPLC method enables reliable quantification of enzalutamide, supporting the development of novel bioavailability-enhancing formulations for effective prostate cancer management.